Comparative Cytotoxicity of Standard of Care Treatment Drugs on Human Breast, Prostate, Colon, Cervical and Hepatic Cancer cell lines - Satish, Smera; Gore, Gayatri; Ganpule, Akshay; Srivastava, Sangeeta; Athavale, Maithili (International Journal of Scientific Research in Biological Sciences, 2020)
Currently there are various standard of care drugs used for the treatment of various cancers. Understanding effectiveness of standard treatment over a broad range of cancer cell lines helps in selecting the most appropriate drug for a particular cancer type. We have performed a comprehensive study for seven standard of care drugs namely Cisplatin, Sunitinib, Carboplatin, Doxorubicin, 5-Fluorouracil, Tamoxifen and Paclitaxel over a panel of Breast (MDAMB231, MDAMB468, T47D), Prostate (DU145, PC3, LNCaP), Colon (COLO205, COLO320DM, HCT-15), Cervical (SiHa, HeLa) and Hepatic (HEP3B) Cancer cell lines for anticancer (tested by MTT Assay) and anticancer stem cell activity (tested by Sphere Assay and Wound Healing Assay, WHA).Our MTT results have indicated that Doxorubicin and Sunitinib are highly potent drugs exhibiting highest activity on SiHa {IC50- 0.24uM (±0.28)} and COLO205 {IC50 -2.64uM (±0.09)}. Paclitaxel also demonstrated very high activity in MTT assay for all cancer types’ especially high potency on co on: COLO205 {IC50-0.045uM (±0.03)}, COLO320DM {IC50- 0.058uM (±0.01)}, HCT15 {IC50- 0.007uM (±0.4)}. Interestingly, these three drugs have also demonstrated very good anti-CSC activity as indicated by ≥ 50% sphere reduction at 250nM for all cancer types and have exhibited remarkable reduction in growth (<30%) at scratch in WHA at the end of 48hrs.Overall, our findings suggest that Doxorubicin, Sunitinib and Paclitaxel have very high anticancer stem cell potential thereby qualifying to be used in combination therapy regimes.